2014
DOI: 10.1590/s1984-82502014000400025
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and stress degradation studies of cefepime/tazobactam in dry injection form by an RP-HPLC method

Abstract: A simple, specific, precise, accurate, linear, rapid, economic and validated stability indicating an RP-HPLC method for the simultaneous quantification of cefepime and tazobactam in a dry injection dosage form has been developed. Separation was performed on a 5 µm ACE C 18 column with phosphate buffer, pH adjusted to 4.5 with phosphoric acid: methanol (70:30) at a flow rate of 1 mL/min and at a temperature of 25 °C. Regression analysis showed linearity at a detector wavelength of 290 nm in the range of 200-600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Finding the most important factors that influenced the features of the liquid-liquid chromatographic separation, such as retention time, relative retention time, peak form and symmetry, tailing factor, and the number of theoretical plates, was one of the goals of this study [13][14][15]. A literature survey revealed that several methods are available for the determination of cefepime in different matrixes individually or in combination with other drugs like second-derivative spectroscopy [16], HPLC [17][18][19], and UPLC [20]. Sulbactam was successfully determined by CITP [21], UV-spectrophotometric [22], and HPLC [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Finding the most important factors that influenced the features of the liquid-liquid chromatographic separation, such as retention time, relative retention time, peak form and symmetry, tailing factor, and the number of theoretical plates, was one of the goals of this study [13][14][15]. A literature survey revealed that several methods are available for the determination of cefepime in different matrixes individually or in combination with other drugs like second-derivative spectroscopy [16], HPLC [17][18][19], and UPLC [20]. Sulbactam was successfully determined by CITP [21], UV-spectrophotometric [22], and HPLC [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat urinary tract infections, septicemia, staphylococcal infections, bronchitis, intra-abdominal infections, skin and its structures infections, pneumonia infections, and in febrile neutropenic patients (Glish and Burinsky, 2008;Lemke et al, 2002). CFP stability was estimated using several methods using chromatography (Abd El Aziz Shama et al, 2021;Al Kamaly, 2022;Bjergum et al, 2021;De Borba et al, 2008;Dos Anjos et al, 2022;El-Beltagy et al, 2019;El-Dars et al, 2019;Fage et al, 2021;Isla et al, 2005;Jagadeesh Kumar et al, 2010;Jiang et al, 2010;Jiménez Palacios et al, 2005;Kalyani et al, 2018;Kommana et al, 2014;Liu et al, 2018;Mameli et al, 2019;Moorthy et al, 2020;Nemutlu et al, 2009, Ocaña González et al, 2004Ohmori et al, 2011;Patil et al, 2018;Rehm and Rentsch, 2020;Rodrigues et al, 2016;Seraisso et al, 2022;Shrestha et al, 2014;Siddiqui et al, 2010;Sun et al, 2022;Sundara Raj et al, 2013;Sunitha et al, 2013;Van Vooren and Verstraete, 2021;Zander et al, 2015) but these methods had some disadvantages as complex mobile phase composition, increased matrix effect, decreased sensitivity, and inability to identify degradants using trace analysis in addition to fragmentation (Niessen, 2010;Niessen and Ricardo, 2017), less environmentally friendly, and time-consuming. However, there have been no previous analytical procedures of trace analysis reported on CFP stability studi...…”
Section: Introductionmentioning
confidence: 99%